Knowledge, attitude, and practice regarding treatment of group a beta hemolytic tonsillo pharyngitis and prevention of rheumatic fever among doctors in Karachi, Pakistan: a perspective study - Arshad Ali Shah; Dil Bahar Shah Asad; Syed Saboor Hasan; Rohan Kumar Ochani; Asim Shaikh; Mukesh Kumar; Dileep Kumar (Journal of the Pakistan Medical Association, 2022)
Objective: To assess knowledge and practices associated with rheumatic fever among medical practitioners in an urban setting. Method: The cross-sectional study was conducted at five major hospitals in Karachi from August to November 2019, and comprised house officers, postgraduate trainees, and general physicians of either gender. The subjects were given a questionnaire assessing their knowledge and perception regarding acute rheumatic fever as well as prophylaxis. Data was analysed using SPSS 25. Results: Of the 247 respondents, 173(70%) were house officers, 31(13%) were postgraduate trainees and 43(17%) were general physicians. Overall, 202(82%) subjects were associated with some teaching hospital. Significantly more postgraduate trainees and general physicians answered correctly when asked to identify clinical and laboratory findings suggestive of Group A streptococcal throat infection than house officers (p<0.001). Among the house officers 49(28.3%), and among the postgraduate trainees 11(35.4%) knew the correct way to prescribe penicillin to prevent rheumatic fever. Among the general physicians, 20(46.5%) had accurate knowledge regarding the prescription. Conclusion: Knowledge and practices of medical practitioners regarding rheumatic fever were less than ideal and may play a part in misdiagnoses of Group A streptococcal infections and, hence, prophylaxis. Key Words: Rheumatic fever, Preventive medicine, Rheumatic heart disease, Pakistan.